Safety of cerebral digital subtraction angiography : complication rate analysis - Usman, Fritz Sumantri; Sani, Achmad Firdaus; Husain, Shakir (Universa Medicina, 2012)
Background Cerebral digital subtraction angiography (DSA) continues to be used for the examination of patients with cerebrovascular diseases. In the past decade, safer contrast agents have been used and there have been important technical advances including smaller catheters, hydrophylic guide wires, and digital imaging systems. The objective of this study was to determine the neurological complication rates of cerebral angiography performed for inpatients. MethodsA prospective study was conducted from January 2009 until December 2011. The patientâs demographic characteristics, the procedural details as well as complications appearing during and after the procedure were documented. Neurological complications are classified based on the international classification: (a) transient, disappearing within 24 hours; (b) reversible, lasting more than 24 hours but less than 7 days; (c) permanent, if the complication last for more than 7 days. The complications were examined by a neurologist.ResultsThe patients comprised 82 (41%) women and 118 (59%) men, ranging from 11 to 86 years of age. From 200 patients who underwent the procedure, permanent neurological complications were found in 1 (0.50 %) patient. Neither reversible nor transient neurological complications were found. ConclusionThe cerebral digital subtraction angiography procedure, when conducted by a neuro interventionist, is relatively save, both from the aspect of neurological and non-neurological complications, and from the number of deaths. The overall neurological complication rate fell within the limits recommended by quality improvement and safe practice guidelines.